PERSONALISASI IKLAN SEBAGAI STRATEGI PEMASARAN ARMINAREKA - Sumarni, Neni; Suroso, Suroso; Suherman, Enjang; Pertiwi, Wike (Jurnal Signaling, 2024)
There needs to be a way or strategy to market a product, both goods and services. The marketing strategy through personalized advertising carried out by Arminareka through marketing or its team leaders has succeeded in attracting its pilgrims or customers, and through personalizing WhatsApp media advertising, it has proven that consumer loyalty, in this case Umrah pilgrims, can be created more effectively and optimally in attracting potential pilgrims. The method used in this research uses qualitative methods with triangulation analysis tools. The marketing mix created with the 7 Ps can maximize the satisfaction of the congregation. High prices are a standard benchmark that proves that the facilities and services obtained are in accordance with what the congregation has spent "there is a price and there is quality"